Ratcheting assessment of notched steel samples subjected to asymmetric loading cycles through coupled kinematic hardening-Neuber rules. (August 2018) - Kolasangiani, K.; Farhangdoost, K.; Shariati, M.; Varvani-Farahani, A.
Highlights: Local ratcheting strains at notched 1045 steel samples were studied over asymmetric stress cycles. Magnitude of notch size and stress range noticeably promoted ratcheting at notch roots. Hysteresis loops and ratcheting at notch roots were predicted through the Neuber's and Chaboche rules. Neuber's rule lacked to assess local stress/strain components and ratcheting at high stress ranges. Abstract: The present study examines local ratcheting at notch root of 1045 steel samples subjected to asymmetric loading cycles. Ratcheting strain values were measured through strain gauges mounted at the vicinity of notch roots for various notch sizes of 3, 6, 9, and 15 mm in diameter. Ratcheting tests were conducted at various cyclic loads of 13 kN ± 13 kN, 16 kN ± 16 kN, 19 kN ± 19 kN, and 25 kN ± 25 kN with load ratio R = 0. Local ratcheting strain were highly influenced by notch diameter and magnitude of the nominal mean/amplitude of loading cycles. Nominal force-controlled cycles were designed to include three ranges of (i) below the elastic limit ( S  <  S0 ), (ii) above elastic limit and below yield stress ( S0  < S  <  Sy ), and (iii) above the yield stress ( S  >  Sy ). The Neuber's rule was employed to accommodate for the local stress and strain components at the notch root over loading, unloading and reloading paths enabling to construct stress–strain hysteresis loops over ratcheting progress. Accumulation of plastic strain at vicinity of notch roots over loading cycles were further analysed by means of the Chaboche hardening model. Predicted local ratcheting strain values and those of measured through strain gauges were compared and the applicability of the Neuber's rule at three different stress ranges were evaluated. The local ratcheting strain while progressed at the notch root over loading cycles resulted in mean stress relaxation controlled by the Chaboche model. Graphical abstract: Image, graphical abstract